Pseudo-Arcadius' Epitome of Herodian's Περὶ καθολικῆς προσῳδίας; with a critical edition and notes on Books 1-8 - Roussou, S (2011)
This thesis is a new edition of the Preface and Books 1-8 of Pseudo-Arcadius’ Epitome of Herodian’s Περὶ καθολικῆς προσῳδίας. It includes an introduction, critical apparatus, apparatus of parallel passages and notes on the text, and is intended as a contribution to modern Herodianic studies. Most of our knowledge of Greek accentuation is due to Herodian’s lost Περὶ καθολικῆς προσῳδίας. The main sources for this work, an epitome misattributed to Arcadius and another by John Philoponus, do not have modern critical editions. Lentz’s only collected edition of Herodian’s works (1867-70) is difficult to work with, because Lentz attempts to reconstruct Herodian’s work rather than to lay out the surviving evidence. The new critical edition of Pseudo-Arcadius’ Epitome is a response to the need for new and separate editions of the sources for the Περὶ καθολικῆς προσῳδίας. A new edition of this text is important because the previous two editions (Barker 1820, Schmidt 1860) have many weaknesses; neither editor examined all the surviving manuscripts, and they did not read the manuscripts themselves but used copies made by other people. My new examination of all the surviving manuscripts, excepting some very late and uncontroversially derivative manuscripts, comes to a new conclusion about their interrelations. The two manuscripts which I am the first to employ turn out to be the only non-derivative manuscripts, and therefore by far the most important. They enable us to improve the text significantly. My introduction includes a substantial new evaluation of the interpolated or doubtful sections in the epitome, whose study is impeded by confusion as to their date and relationships to other works. It also discusses the authorship of this epitome, and its grammatical terminology and concepts. Another innovation is the apparatus of parallel passages. The collection of other texts that have derived material from Herodian shows the extent of Herodian’s influence on later grammatical texts. The parallel passages, as witnesses to Herodian’s text in some form, often enable us to correct the text of Pseudo-Arcadius’ Epitome. A further contribution of my thesis consists of the commentary, which discusses corrupt passages, features of the text that have never been explained before, and places where specific details of the epitomator’s methods can be identified. The commentary also provides argumentation supporting decisions taken in editing the text, and other helpful information for the understanding of the text.